Strategic and Legal Alternatives in Case of Adverse Organizational Crisis Results. The Bulgarian Case - BACHVAROVA, Margarita St.; ZAFIROVA, Tzveta J. (Journal of Advanced Research in Law and Economics; Vol 8 No 2 (2017): Volume VII, Issue 2(24), Spring 2017, 2017)
Based on an interdisciplinary approach this article studies the problems of the alternatives to adverse organizational crises results in the presence of financial straits and insolvency. It has inquired into the standpoints of various scientists on the forms of occurrence of the organizational crises, by giving emphasis to the possibilities in the last form – liquidity crisis in case of a negative outcome. It has explained what strategic alternatives could be applied in such a situation according to the specialized literature in this area. The relation is searched within the process of selection of a strategic alternative with a view to the most favorable legal regime depending on the legislation of the respective country. Analysis has been made of the empirical data for the period 2008-2015 of the dynamics connected with the effect of the insolvency legal framework in Bulgaria, as well as the insolvency proceedings development in order to demonstrate the Bulgarian legal framework in this area and its specific features.